Resin flow analysis during RTM Manufacturing of GFRP composites containing embedded impermeable inserts (Research, Society and Development, 2021)
The aim of this work is to analyze resin flow during RTM manufacturing of GFRP composites containing embedded impermeable inserts. High-density polyethylene inserts were embedded in the composites during processing via vacuum assisted resin transfer molding (RTM). The processing station plate was assembled so that digital image analysis of flow during and after processing could be taken. Three-point bending test specimens were cutout from the plates and their fractured surfaces were analyzed by optical fractography.  Results indicate the inserts to block transverse resin flow making it difficult to wet the fibers thoroughly, which led to non-uniform plate thickness.  Resin rich regions near the sides of the inserts were observed. Three-point bending failure mode analysis showed the occurrence of fiber delamination by type II shear stress, detachment between the fiber/matrix interface and the insert, and fracture of the composite to proceed by crack propagation through the resin rich region.